Obesity and the role of genetic polymorphism: A review of genes as the risk of obesity - Pramudji Hastuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Obesity can be caused by environmental factors, which are higher energy input or lower energy expenditure. Environmental factors supported by genetic factors cause a person to have a different risk for developing obesity from to another. Genetics factors cause obesity through several pathways, which are impaired regulation in the hypothalamus and the regulation of energy expenditure. Obesity may be caused by one gene as monogenic-associated obesity, however, commonly caused by several genes together with environmental factors as the main multi-factorial risk of obesity. Obesity causes inflammation which leads to metabolic diseases. Many efforts are performed to prevent or treat obesity through the intervention to environmental and or genetic factors. Many attempts to reduce the prevalence of obesity were performed by influencing the environmental risk factors or the genetic risk factors. In this review, we identified the main genes which influence obesity. The genetic risks of obesity may be different from one to another country or between ethnic groups. Therefore, a better treatment approach should consider the differences role of genes in obesity rather than only changes in lifestyle. Nutrigenetic approach by considering the difference role of gens in responding to nutrients or drugs is recommended in individualized treatment plans.